Effect of high‐flow vs. low‐flow nasal plus mouthguard oxygen therapy on hypoxaemia during sedation: a multicentre randomised controlled trial. (28th June 2021) - Thiruvenkatarajan, V.; Dharmalingam, A.; Arenas, G.; Wahba, M.; Liu, W.-M.; Zaw, Y.; Steiner, R.; Tran, A.; Currie, J.
Summary: Whether high‐flow vs. low‐flow nasal oxygen reduces hypoxaemia for sedation during endoscopic retrograde cholangiopancreatography is currently unknown. In this multicentre trial, 132 patients ASA physical status 3 or higher, BMI > 30 kg.m ‐2 or with known or suspected obstructive sleep apnoea were randomly allocated to high‐flow nasal oxygen up to 60 l.min ‐1 at 100% FI O2 or low‐flow nasal oxygen at 4 l.min ‐1 . The low‐flow nasal oxygen group also received oxygen at 4 l.min ‐1 through an oxygenating mouthguard, totalling 8 l.min ‐1 . Primary outcome was hypoxaemia, defined as Sp O2 < 90% regardless of duration. Hypoxaemia occurred in 7.7% (5/65) of patients with high‐flow and 9.1% (6/66) with low‐flow nasal oxygen (percentage point difference −1.4%, 95%CI −10.9 to 8.0; p = 0.77). Between the groups, there were no significant differences in frequency of hypoxaemic episodes; lowest Sp O2 ; peak transcutaneous carbon dioxide; hypercarbia (transcutaneous carbon dioxide > 2.66 kPa from baseline); requirement of chin lift/jaw thrust; nasopharyngeal airway insertion; bag‐mask ventilation; or tracheal intubation. Following adjustment for duration of the procedure, the primary outcome remained non‐significant. In high‐risk patients undergoing endoscopic retrograde cholangiopancreatography, oxygen therapy with high‐flow nasal oxygen did not reduce the rate of hypoxaemia, hypercarbia or the need for airway interventions, compared with combined oral and nasal low‐flow oxygen.